2020
DOI: 10.1371/journal.pone.0237746
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-mediated adhesive properties of neutrophils are reduced by hyperbaric oxygen therapy in patients with chronic non-healing wound

Abstract: In recent years, several studies suggested that the ability of hyperbaric oxygen therapy (HBOT) to promote healing in patients with diabetic ulcers and chronic wounds is due to the reduction of inflammatory cytokines and to a significant decrease in neutrophils recruitment to the damaged area. α 4 and β 2 integrins are receptors mediating the neutrophil adhesion to the endothelium and the comprehension of the effects of hyperbaric oxygenation on their expression and functions in neutrophils could be of great i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 70 publications
(109 reference statements)
1
15
0
3
Order By: Relevance
“…In a prospective randomized trial with 32 patients suffering from diabetic foot ulcers, supportive HBO was able to promote wound healing by stimulating angiogenesis, decreasing inflammation, and increasing the nitrite levels [ 5 ]. Similar results were obtained in another clinical study which proved the anti-inflammatory efficacy of HBO in patients with chronic diabetic wounds [ 6 ]. Moreover, in a prospective clinical trial involving 27 patients with diabetic food ulcers, adjunctive HBO resulted in accelerated wound healing by stimulating the vascular endothelial growth factor and the epidermal growth factor [ 7 ].…”
Section: Clinical Impact Of Hbo On the Different Molecular Mechanismssupporting
confidence: 89%
“…In a prospective randomized trial with 32 patients suffering from diabetic foot ulcers, supportive HBO was able to promote wound healing by stimulating angiogenesis, decreasing inflammation, and increasing the nitrite levels [ 5 ]. Similar results were obtained in another clinical study which proved the anti-inflammatory efficacy of HBO in patients with chronic diabetic wounds [ 6 ]. Moreover, in a prospective clinical trial involving 27 patients with diabetic food ulcers, adjunctive HBO resulted in accelerated wound healing by stimulating the vascular endothelial growth factor and the epidermal growth factor [ 7 ].…”
Section: Clinical Impact Of Hbo On the Different Molecular Mechanismssupporting
confidence: 89%
“…In a small study with 17 patients, hyperbaric oxygen therapy was noted to induce cytoplasmic translocation of HIF-1a and nuclear factor (NF)-kB localization as well as increased VEGF, IL-6, insulin-like growth factor binding protein 3, adiponectin, fibrosis, and angiogenesis while decreasing interferon (IFN)-γ levels [ 148 ]. In addition, the prolonged use of hyperbaric oxygen therapy has also been shown to decrease the recruitment and adhesion of neutrophils, increase oxygen dispersion to damaged tissues, reduce inflammation, and accelerate healing in patients with diabetic ulcers [ 149 , 150 , 151 ]. More recently, studies of topical oxygen therapy rather than HBOT have been shown to promote healing in DFUs and promote an aerobic wound microbiome [ 152 , 153 ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Wound healing is a complex and tightly structured process that requires a well-orchestrated interaction of molecular and cellular events, in which it is divided into several stages, among them: hemostasis, inflammation, re-epithelialization, and tissue remodeling. The activation of the immune system is also part of this stage, acting directly to remove dead cells and matrix debris from the damaged tissue (Baiula et al, 2020).…”
Section: Discussionmentioning
confidence: 99%